TANGGUNG JAWAB PEMERINTAH TERHADAP PEMBERIAN BANTUAN HUKUM BAGI MASYARAKAT MISKIN DI PROVINSI ACEH - Setiawati, Ilyas Ismail, Mujibussalim. (Jurnal Ilmu Hukum, 2016)
Abstract: Government policy in the provision of legal assistance to the legal aid recipients is organized by the Ministry and implemented by legal assistances according to Act No. 16 Year 2011 regarding Legal Aid. An equal provision of legal aid has not yet been implemented and evenly distributed in all districts or cities in Aceh. The aim of this study is to describe the implementation’s responsibility of governmnet by the provision of legal aid, obstacles, and the conducted efforts by the provision of legal aid, especially for the poor in Aceh. The method applied in this study is social juridistic. The implementation of legal assistance has been done by the verified and accreditized legal aid providers, as well as operator regulator in legal aid financial disbursement, monitoring and evaluation by the legal aid implementation. Obstacles that have been indentified during its implementation are: i) there have been no coordination among the internal institutions belong to the Ministry of Justice and Human Rights, ii) lack of socialization regarding the availability of legal aid in the community, iii) inadequate number of lawyers compared to the number of poor people, while most of the legal aid organizations available only big cities. It is suggested to the Regional Office of Ministry of Law and Human Rights in Aceh to intesively strenghten its coordination with the law enforcement authorities and to conduct verification and accreditation programs in order to support the existence of legal aid organizations in each district  or city.Keywords : responsibility, government, legal aid. Abstrak: Kebijakan pemerintah dalam pemberian bantuan hukum kepada penerima bantuan hukum diselenggarakan oleh Menteri dan dilaksanakan oleh pemberi bantuan hukum berdasarkan Undang-Undang Nomor 16 Tahun 2011 tentang Bantuan Hukum. Pemerataan pemberian bantuan hukum belum terlaksana dan belum tersebar merata di seluruh kabupaten/kota di Aceh. Tujuan dari penelitian ini untuk menjelaskan tanggung jawab pelaksanaan pemerintah dalam pemberian bantuan hukum, kendala yang dihadapi, serta upaya yang dilakukan dalam pemberian bantuan hokum, khususnya bagi masyarakat miskin di Aceh. Metode penelitian yang digunakan pada penelitian ini adalah yuridis sosiologis. Pelaksanaan bantuan hukum dilakukan oleh pemberi bantuan hukum yang terverifikasi dan terakreditasi, serta sebagai regulator operator dalam penyaluran dana bantuan hokum, pengawasan dan evaluasi pelaksanaan bantuan hukum. Kendala yang timbul dalam pelaksanaan pemberian bantuan hukum adalah: i) belum adanya koordinasi diantara institusi internal dari Kementerian Hukum dan HAM, ii) kurangnya sosialisasi megenai keberadaan bantuan hukum di masyarakat, iii) jumlah advokat yang tidak memadai dibanding jumlah masyarakat miskin, sementara itu kebanyakan organisasi bantuan hukum berada di kota-kota besar. Disarankan kepada Kantor Wilayah Kementerian Hukum dan HAM Aceh agar lebih meningkatkan koordinasi antara Aparat Penegak Hukum dengan lebih intensif dan melakukan program-program verifikasi dan akreditasi untuk mendorong keberadaan organisasi pemberi bantuan hukum di setiap kabupaten/kota.Kata kunci : tanggung jawab, pemerintah, bantuan hukum.